Konstruksi teoretik modul konseling interkultural dalam penanganan bullying di sekolah dasar multikultural - Ferdiansyah, Muhammad; Lubis, Muhammad Alridho; Zubaidah, Zubaidah; Zulfikar, Muhammad (Proceedings Academic Universitas Jambi, 2025)
Bullying in multicultural elementary schools in Jambi Province has shown an alarming increase, posing serious threats to children’s psychosocial development. This study aims to (1) explore the experiences of teachers, counselors, and students in addressing bullying at the elementary school level; (2) identify intercultural values relevant to counseling practices; and (3) construct a conceptual framework for an intercultural counseling module rooted in Jambi’s local wisdom. A qualitative approach with grounded theory was employed, involving the stages of open coding, axial coding, and selective coding. Data were collected through in-depth interviews, participant observations, and focus group discussions and validated through source triangulation, expert review, and limited dissemination. The findings indicate that bullying is influenced by three main factors: (1) individual factors, such as low self-control and lack of empathy; (2) socio-cultural factors, including the dominance of seniority norms, cultural acceptance of violence, and peer pressure; and (3) school environment factors, including limited teacher supervision and the absence of systematic anti-bullying policies. The grounded theory produced a conceptual construction of an intercultural counseling module that integrates cross-cultural empathy, local wisdom, and both preventive and curative counseling strategies tailored to multicultural. The novelty of this study lies in the development of an intercultural counseling module based on Jambi’s local culture, designed to be both theoretical and practical. The implications provide conceptual and practical contributions to the field of guidance and counseling, particularly intercultural counseling, and offer a culturally grounded intervention instrument to enhance the effectiveness of bullying prevention in multicultural elementary schools.